LABORATORY TESTING RESULTS ANALYSIS OF GIARDIASIS PREVALENCE AMONG DIFFERENT POPULATION GROUPS IN THE NENETS AUTONOMOUS DISTRICT - N. S. Bobyreva (Sankt-Peterburg : NIIÈM imeni Pastera, 2015)
The Nenets Autonomous District (NAD) refers to the territories of the Russia’s Far North. The country is the only region of Russia, where there are still no roads. The extreme weather conditions, as well as residential patterns in the NAD reduce the availability of specialized medical care, as indigenous people and other nationalities living in the district, which requires the use of health care management specific forms. The article presents data on giardiasis studies amongst different categories of the NAD population, obtained as a result of the population surveys in remote regions of the Russian Federation Arctic zone. Samples studied were serum and faecal emulsion. The study used the following laboratory methods: for serum — Giardia lamblia antibody screening method using ELISA kit, emulsion stool — native smear microscopy analysis, the method of enrichment using disposable concentrators «Parasep» immunological diagnostic methods based on the detection of specific lamblia antigen in faeces using ELISA kits. For statistics was used descriptive statistics analysis (mean values, the percentage error of the mean, the construction of the trend line) with program SPSS 20.00, Excel 2010, the method of analysis of official statistical reporting hospitals survey on giardiasis, data of Rospotrebnadzor (Russian Sanitary service) for NAD and data from own research from 2002 to 2013. Just in the process of research carried out research on the 10 356 giardiasis, registered diseases by 3470 cases of giardiasis, accounting for 99.14% of the total number of protozoonosises registered and 37.4% of all registered in the NAD parasitosis. The comparison was made among the population of the county towns, home to both the indigenous people, nomadic, and representatives of other ethnic groups, sedentary with urban population of the city of Naryan-Mar. The article analyzes the incidence rates for giardiasis according to district official statistical reporting compared with the incidence in the Russian Federation for the same period of time. Statistical analysis was performed using the software package Excel 2010. The study found an association of giardiasis prevalence in the population of the NAD on criteria such as location, gender, occupation and age structure examined.